2017
DOI: 10.4049/jimmunol.1700021
|View full text |Cite
|
Sign up to set email alerts
|

Limited Presence of IL-22 Binding Protein, a Natural IL-22 Inhibitor, Strengthens Psoriatic Skin Inflammation

Abstract: Psoriasis is a chronic inflammatory disease resulting from dysregulated immune activation associated with a large local secretion of cytokines. Among them, IL-22 largely contributes to epithelial remodeling and inflammation through inhibiting the terminal differentiation of keratinocytes and inducing antimicrobial peptides and selected chemokines. The activity of IL-22 is regulated by IL-22 binding protein (IL-22BP); however, the expression and role of IL-22BP in psoriatic skin has remained unknown so far. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“…study in which administration of recombinant IL-22BP-Fc resulted in an increase in PMN counts in a cecal legation puncture model of microbial sepsis 40 . More recently, we showed in the imiquimod-induced psoriasis model in mice, known to be IL-22 dependent, that in vivo neutralisation of IL-22BP with the same neutralising antibody used in the present study led to increased severity of psoriasis-like skin inflammation 41 . Taken together, our data highlighted the role of the IL-22/IL-22BP system during bacterial pneumonia and the need for additional studies to assess its therapeutic interest for patients suffering from bacterial pneumonia or ARDS.…”
Section: Discussionsupporting
confidence: 58%
“…study in which administration of recombinant IL-22BP-Fc resulted in an increase in PMN counts in a cecal legation puncture model of microbial sepsis 40 . More recently, we showed in the imiquimod-induced psoriasis model in mice, known to be IL-22 dependent, that in vivo neutralisation of IL-22BP with the same neutralising antibody used in the present study led to increased severity of psoriasis-like skin inflammation 41 . Taken together, our data highlighted the role of the IL-22/IL-22BP system during bacterial pneumonia and the need for additional studies to assess its therapeutic interest for patients suffering from bacterial pneumonia or ARDS.…”
Section: Discussionsupporting
confidence: 58%
“…Functional studies using IL-22BP-deficient rodents have shown a protective role for IL-22BP in ischemia reperfusion and acetaminophen-induced liver injury (69). In rats, deficiency of IL-22BP led to exacerbated skin disease in a psoriasis model that was associated with increased IL-22 and antimicrobial peptides (70). IL-22BP has been proposed to have therapeutic potential.…”
Section: How Does Il-22 Binding Protein Regulate Il-22 Biology?mentioning
confidence: 99%
“…47 ] and reduced expression of IL-22BP only exacerbates this process. 48,49 In the intestine, where IL-22 is constitutively expressed to protect the mucosal surface, 50 Il22ra2 −/− mice develop greater number of tumors in a colitis cancer model. 15 Therefore, too much IL-22 can have negative consequences.…”
Section: Discussionmentioning
confidence: 99%